Perception towards physical activity, quality of life, social support and environment by elderly people who participate in a physical activity program - Moya Castro, Diego Francisco (2023)
The aim of this study was to determine the perception towards physical activity, the quality of life, social support and environment of the elderly who participate in a physical education program of the University of Costa Rica. A qualitative study was developed through observation, incomplete phrases and semi-structured interviews. There was a specific sample, 10 senior citizens ages 65 to 85, who attend physical education classes at the University of Costa Rica´s Campus in Grecia. Data analysis was carried out by a triangulation of theories, contrasting the obtained information with the ecological model of Bronfenbrenner at intrapersonal, interpersonal and organizational level. Results shown that through physical activity, participants have seen improvements on their physical skills, mental health and spirituality. They are also aware of the benefits, independence and security receiving through these activities in daily life. Furthermore, it was found that peer and family support is essential for adherence to physical activity. It was concluded that physical activity generates the elderly’s overall improvement, and the support they receive is essential for adherence and enjoyment. Besides, environmental conditions must be adequate to the needs of this population in order to improve their quality of life.